Marital duration in China: Trends and gender differences, 1982–2015 - Zhu, Yingrun; Yu, Xiao; Jiang, Quanbao (Frontiers in Public Health, 2022)
Objectives With the postponement in age at marriage, increase in life expectancy, and acceptance of divorce in China, the marital duration in each state has changed gradually. This study seeks to depict the trends and gender differences of marital duration in China from 1982 to 2015. Design We calculated and depicted the trends of and gender differences in marital duration, including single, marriage, divorce, widowhood duration and the proportion of each duration to the remaining life expectancy at 15. Results The single duration of Chinese men and women was slightly reduced and then extended, with that of men longer than women, showing a narrowing trend in gender difference. The marriage duration of Chinese men and women is lengthening, with that of women longer than men, demonstrating a widening gap in gender difference. However, the proportion of marriage duration in life expectancy at age 15 increased and then declined, with that of men higher than women. The divorce duration of Chinese men and women slightly reduced and then lengthened, but men tend to stay divorced for longer periods than women, and the gender difference is narrowing. The widowhood duration of Chinese men and women is shortening, with women having longer widowhood than men, and the gender difference has been shrinking. Conclusions With the socio-economic and demographic transition, the marital duration in each state has changed gradually, and will have an important impact on fertility level and pension burden.